Mode of Delivery and Fetomaternal Outcomes in Gestational Diabetes Mellitus - Shujat, Spogmay; Bibi, Hajra; Jahan, Gulbakhtha (Indus Journal of Bioscience Research, 2025)
Background: Gestational diabetes mellitus (GDM) is one of the most common complications of pregnancy, frequently linked to negative consequences for both the mother and the child. It may influence the course of labor and often prompts decisions regarding the safest mode of delivery. To determine the frequency of various modes of delivery and assess the associated fetomaternal outcomes in women diagnosed with GDM. Methods: This descriptive cross-sectional study was conducted over six months at a Hayatabad Medical Complex, Peshawar from March 15, 2024 to September 15, 2024. A total of 101 pregnant women with GDM were enrolled using a non-probability consecutive sampling technique. Baseline characteristics, mode of delivery, and outcomes such as pregnancy-induced hypertension, vulvovaginitis, neonatal hyperbilirubinemia, and macrosomia were documented. Data were analyzed using SPSS v26, with the Chi-square test applied to determine associations. Results: Cesarean section was the most common mode of delivery, observed in 60.4% of patients. Pregnancy-induced hypertension was recorded in 35.6% of participants, macrosomia in 13.9%, hyperbilirubinemia in 14.9%, and vulvovaginitis in 6.9%. No statistically significant association was found between mode of delivery and these outcomes (p > 0.05), although macrosomia and hyperbilirubinemia showed trends toward significance. Conclusion: Cesarean section remains a frequently chosen mode of delivery in women with GDM, often driven by precautionary clinical judgment. While complications such as PIH and macrosomia are common, individualized care and effective glycemic control are key to improving fetomaternal outcomes and reducing unnecessary operative deliveries.